New experimental approach on the determination of condensation heat transfer coefficient using frictional pressure drop and void fraction models in a vertical tube - Dalkilic, A. S.; Wongwises, S. (PERGAMON-ELSEVIER SCIENCE LTD, 2010)
The comparison of 35 void fraction and 13 two-phase frictional pressure drop models and correlations with experimental results for the condensation of R134a in a 0.5 m vertical copper tube with an inner diameter of 8.1 mm and outer diameter of 9.52 mm are presented. The most predictive ones having a relation with the heat transfer coefficient at different vapor qualities (0.69-0.96). various mass fluxes (260 and 515 kg m(-2) s(-1)), and different condensing temperatures (40 and 50 degrees C) are proposed. Three of 13 models belonging to the determination of two-phase frictional pressure drop and 8 of 35 models belonging to the determination of void fraction are found to be in good agreement, predicting the condensation heat transfer coefficient by means of von Karman's universal velocity distribution and Kosky-Staub's annular flow film thickness model with their deviations being within the range of +/- 30% for all tested conditions. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Two-phase flow; Condensation; Pressure drop; Heat transfer coefficient; R134a; ADIABATIC 2-PHASE FLOW; HIGH-MASS FLUX; DOWNWARD FLOW; FILM CONDENSATION; AIR-WATER; SMOOTH; REFRIGERANTS; PREDICTION; CHANNELS; Thermodynamics; Energy & Fuels; Mechanics